Physiological responses after two different Crossfit workouts - Forte, L. D. M.; Freire, Y. G. C.; Júnior, J. S. D. S.; Melo, D. A.; Meireles, C. L. S. (Biology of Sport, 2022)
The present study aimed to investigate the physiological response to CrossFit "workouts of the day" (WODs) based on two different structures of training session: 1) the "as many repetitions as possible" (AMRAP) "Cindy" and 2) the "round for time" (RFT) "Open 18.4" session. CrossFit athletes (11 men and 12 women) were divided into two groups: 1) one performing the WOD "Cindy" (GC) and 2) one performing the WOD "Open 18.4" (GO). Before, immediately after and 30 min after WODs, blood lactate (LAC), heart rate (HR) and systolic and diastolic blood pressures (SBP and DBP) were measured. A two-way ANOVA indicated differences in physiological responses between GC and GO. Both WODs increased HR to similar levels. Only GO significantly increased SBP immediately after exercise compared to the rest period (p < 0.01), with no difference to GC. GO presented higher levels of LAC immediately after exercise compared to GC (15.8 ± 4.9 mM [GO] vs 9.3 ± 2.3 mM [GC]; p < 0.01). LAC remained different between the groups 30 min after exercise (7.0 ± 3.9 mM [GO] vs 3.9 ± 0.9 mM [GC]; p < 0.01). The results suggest that the studied WODs do not differ in acute cardiovascular responses, but depend on different metabolic demands, with RFT structure relying more on glycolytic metabolism (indicated by greater LAC levels after exercise in GO). Such results are in agreement independent of gender.